High speed modulated wavelength division optical fiber transmission systems performance signature - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed; Ismail A. Abd El Aziz (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This study presents modulated-wavelength division radio signals over fiber with mixed modulation techniques in the transmitter stage. Hybrid optical sources are used to achieve optimal performance and enhancement for an optical fiber communication network. The proposed modulation techniques work at a frequency of 250 GHz. Optical quadrature phase shift keying (OQPSK) and phase modulation (PM) techniques were merged to create OQPSKPM. This was in addition to the minimum shift keying (MSK) modulation scheme that was applied in the proposed model. The modulated wavelength division multiplexing design to four subscribers was examined with a single mode optical fiber at a 1550 nm wavelength. The proposed and previous simulation models were executed, investigated and measured on important operating parameter quantities that expressed the behavior of the optical fiber network in detail, like maximum quality factor, minimum bit error rate, and output power. The obtained simulation results demonstrated the priority of the proposed simulation model.